The influence of dispositions and shared leadership on team–member exchange. Issue 3 (4th March 2021) - Lau, Rebecca S.; Cheung, Gordon W.; Cooper–Thomas, Helena D.
Abstract : Purpose: This study aims to examine two individual dispositions, propensity to trust and reciprocation wariness, as antecedents of team–member exchange (TMX) and how shared leadership moderates these relationships. It also investigates work engagement as a consequence of TMX. Design/methodology/approach: Data were collected from 175 employees in 42 teams; a multilevel random slope model was used to test the moderating effect of shared leadership at the team level and across levels. Findings: Shared leadership provides a boundary condition for the relationships from propensity to trust and reciprocation wariness to work engagement through TMX. At the individual level, the positive effects of propensity to trust and negative effects of reciprocation wariness on TMX, and their indirect effects on work engagement through TMX, were weaker at higher shared leadership. At the team level, the positive relationship between propensity to trust and TMX was unconditional on shared leadership, whereas the relationship between reciprocation wariness and TMX was moderated by shared leadership. At the team level, shared leadership had positive effects on TMX and work engagement. Practical implications: Managers can adopt shared leadership to encourage social exchanges among team members to enhance TMX and work engagement. Originality/value: The study extends the TMX research by investigating dispositions as antecedents and work engagement as a consequence at both individual and team levels. It also identifies the moderating role played by team-level shared leadership, which provides a strong situation supporting reciprocal interactions.